2013
DOI: 10.1021/jf403538y
|View full text |Cite
|
Sign up to set email alerts
|

Controllable Self-Assembly of Sodium Caseinate with a Zwitterionic Vitamin-Derived Bolaamphiphile

Abstract: The control of self-assembly of sodium caseinate (SC) including the formation of mixed layers, microspheres, or nanoparticles is highly relevant to the microstructure of food and the design of promising drug delivery systems. In this paper, we designed a structure-switchable zwitterionic bolaamphiphile, 1,12-diaminododecanediorotate (DDO), from orotic acid, which has special binding sites and can guide the self-assembly of SC. Complexation between SC and DDO was investigated using dynamic light scattering, tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…21 ITC is a sensitive technique that thermodynamically characterizes equilibrium reactions involving a small molecule ligand and biomolecules. By using this technique, we have determined the molecular mechanisms behind flavor sensations, 22 the structural transitions of food proteins, 23 and interactions between endogenous compounds and food components. 16 Systematic investigations of the thermodynamic differences between MCFA and LCFA binding to BSA by using ITC have not been well documented.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…21 ITC is a sensitive technique that thermodynamically characterizes equilibrium reactions involving a small molecule ligand and biomolecules. By using this technique, we have determined the molecular mechanisms behind flavor sensations, 22 the structural transitions of food proteins, 23 and interactions between endogenous compounds and food components. 16 Systematic investigations of the thermodynamic differences between MCFA and LCFA binding to BSA by using ITC have not been well documented.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Besides the work that deals with the micelle behavior of the binary surfactant system, solubilization of vesicles by bile salts has attracted considerable attention because these systems can be used to simulate biological processes and contribute to a better understanding of absorption phenomena within the small intestine. To date, thermodynamics and structural evolution of vesicles induced by bile salts were obtained mainly from classical bilayers formed from phospholipids; only a few studies focused on the synthetic vesicle built by the mixture of anionic and cationic surfactants at certain conditions. , We previously found that zwitterionic vitamin-based bolaamphiphiles derived from orotic acid, 1,12-diaminododecanediorotate (DDO), could form a stable monolayer vesicle spontaneously and guide the self-assembly of sodium caseinate . This bolaamphiphile represents a potential dietary surfactant and can serve as a typical monolayer vesicle.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the studies dealing with the impact of surfactants on the supramolecular organization of the main milk proteins, caseins, have been conducted with anionic or nonionic surfactants. , Data on the interaction with cationic surfactants are relatively scarce. One of the interesting features of the mixture of oppositely charged amphiphilic molecules is that the self-assembled structures and the charge of their electrical double layer can be manipulated by simple variation of concentrations and molar ratio of components.…”
Section: Introductionmentioning
confidence: 99%